ANALYSIS AND MODELING OF THE SOCIAL SECURITY INDEX IN UKRAINE, LITHUANIA, AND SCANDINAVIAN COUNTRIES - Stavytskyy, Andriy V.; Sadovenko, Oksana V. (Ekonomika, 2013)
Abstract. The social security of acountry is a situation which is positively regulated by legal norms where the government uses all democratic management practices to maintain decent living standards and ensure the ability to meet basic needs for the development of the country and society. The Scandinavian economic model provides for a comprehensive social protection and social benefits to all segments of the community. That is why we used a comparative analysis and the modelling of the social security index in Ukraine, Lithuania, and Scandinavian countries. In the paper, we identify a unique method for calculating the indicator of social security, using three main components: income, demographic situation, and labour market. We have studied the impact of macroeconomic indicators on the level of social security, made an analogy with the Nordic countries, and determined which model should be used for the best results in ensuring the social protection of society. The research has shown that high tax rates combined with a full public confidence in the government and a transparent system of income redistribution are important factors in the development of socially-oriented Scandinavian countries. A regression analysis was conducted to analyse the relationship of tax revenues and social security index; the models of dependence for each country were constructed. We have defined the basic types of taxes and their impact on the economic situation in a country. It is concluded that, in most cases, increasing tax rates should lead to negative changes in the social security of a country. Key words: social security, public policy, fiscal policy, stability, society